Beyond taro leaf blight: A participatory approach for plant breeding and selection for taro improvement in Samoa - Hunter, D.G.; Iosefa, T.; Delp, Charles J.; Fonoti, P. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
The 1993 outbreak of leaf blight in Samoa resulted in the devastation of the staple taro crop and farmer's incomes from local and overseas markets. The preferred cultivars were all susceptible to the disease, and attempts to solve the problem through fungicides and changed cultural practices have had little impact Efforts to evaluate exotic cultivars and breed taro with disease resistance commenced in 1996. Recent initiatives to facilitate the breeding program in Samoa include a university breeders' club and the Taro Improvement Project (TIP), involving university and ministry research staff, students, extension staff, and farmers. Both initiatives have been motivated by an interest in greater participation of students and farmers in the breeding process and evaluation of introduced taro cultivars. This paper reviews and evaluates experiences in Samoa with participatory approaches to plant breeding using a breeders' club and a fanners' group (TIP), highlighting the benefits of both.